The status of information systems research in Australia: preliminary results - Pervan, Graham; Cecex-kecmanovic, D. (Southern Cross University, 2001)
As the first stage of a study to investigate the status of Information Systems research in Australia, a survey of the heads of all IS discipline groups in Australian universities was conducted. The study revealed a wide range of topics researched (with rapid growth in Electronic Commerce and Knowledge Management), a range of foci, a balance between positivist and interpretivist research, survey was the most frequently used research method, and most research was directed at informing IS professionals. A SWOT analysis provided some further interesting results.